SHG-Bank linkage programme - a study in Thrissur district - Vijitha V N (Department of Rural Banking and Finance Management, College of Co-operation Banking and Management, 2008)
Self Help Groups have been recognized by the policy makers as an effective tool for accomplishing the distributional objectives of monetary policy. The SHG model with bank lending to groups of poor women without collateral has become an accepted part of rural finance. With over 11 million poor households accessing banking services including micro credit through their 29,24,973 SHGs, the SHG-Bank Linkage Programme led by NABARD in India claims to be the largest and fastest growing micro finance programme in the world.